Performance of the cold powered diodes and diode leads in the main magnets of the LHC. Issue 1 (November 2015) - Willering, G P; Giloux, C; Bajko, M; Bednarek, M; Bottura, L; Charifoulline, Z; Dahlerup-Petersen, K; Dib, G; D'Angelo, G; Gharib, A; Grand-Clement, L; Bermudez, S Izquierdo; et al.
Abstract: During quench tests in 2011 variations in resistance of an order of magnitude were found in the diode by-pass circuit of the main LHC magnets. An investigation campaign was started to understand the source, the occurrence and the impact of the high resistances. Many tests were performed offline in the SM18 test facility with a focus on the contact resistance of the diode to heat sink contact and the diode wafer temperature. In 2014 the performance of the diodes and diode leads of the main dipole bypass systems in the LHC was assessed during a high current qualification test. In the test a current cycle similar to a magnet circuit discharge from 11 kA with a time constant of 100 s was performed. Resistances of up to 600 μΩ have been found in the diode leads at intermediate current, but in general the high resistances decrease at higher current levels and no sign of overheating of diodes has been seen and the bypass circuit passed the test. In this report the performance of the diodes and in particular the contact resistances in the diode leads are analysed with available data acquired over more than 10 years from acceptance test until the main dipole training campaign in the LHC in 2015.